2004
DOI: 10.1126/science.1101271
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comments on "Managing Soil Carbon"

Abstract: We agree with Renwick et al. (1) and Van Oost et al.(2) that the magnitude of organic carbon lost from cultivated soils by erosion and mineralization processes is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Charcoal C was greater in the surface-horizon samples of the poorly drained soils than in those of the well drained soils (Table 3), probably the result of water or wind erosion from higher landscape positions and deposition in low spots on the landscape. The enrichment of organic C in depositional landscape positions of agricultural fields is widely appreciated (e.g., Lal et al, 2004;Oost et al, 2004). In studies of steeply sloping (46%) Ultisols and Alfisols under slash-and-burn cultivation and with a mean annual precipitation of 1400 mm, Rumpel et al (2006a,b) have demonstrated that black carbon can be mobilized with eroded sediments.…”
Section: Soilmentioning
confidence: 99%
“…Charcoal C was greater in the surface-horizon samples of the poorly drained soils than in those of the well drained soils (Table 3), probably the result of water or wind erosion from higher landscape positions and deposition in low spots on the landscape. The enrichment of organic C in depositional landscape positions of agricultural fields is widely appreciated (e.g., Lal et al, 2004;Oost et al, 2004). In studies of steeply sloping (46%) Ultisols and Alfisols under slash-and-burn cultivation and with a mean annual precipitation of 1400 mm, Rumpel et al (2006a,b) have demonstrated that black carbon can be mobilized with eroded sediments.…”
Section: Soilmentioning
confidence: 99%
“…The depletion of SOC stock causes a decrease in productivity with the loss of SOM exceeding the C input in oxidative areas as compared to natural ecosystems (Guzman and Al-Kaisi 2010a). Loss of SOC with intensive tillage systems (an ecosystem disservice) may approach 20 to 50 Mg ha -1 (8.92 to 22.3 tn ac -1 ) in 5 to 50 years following conversion from a natural ecosystem to conventional agriculture cropping systems (Davidson and Ackerman 1993;Lal 2004) depending on climate, soil type, drainage class, crop rotations, tillage systems, and residue management (Guzman and Al-Kaisi 2010b). The amount of oxidizable organic materials depends on the type of organic pool (active, passive, or recalcitrant).…”
Section: Role Description Of Ecosystem Servicementioning
confidence: 99%
“…The organic process which involves all the three stages of detachment, transport, and deposition can be more complicated. In the erosion region, with the decrease of soil fertility due to organic carbon loss in the top layer, crop residue returning into the soil carbon pool also declines (Lal et al, 2004b). Simultaneously, the decomposition of organic carbon slows down because of the decrease in fresh carbon supply (Fontaine et al, 2007).…”
Section: Introductionmentioning
confidence: 98%